Active Reconfigurable Tristable Square‐Twist Origami - Wang, Li‐Chen; Song, Wei‐Li; Zhang, Ya‐Jing; Qu, Mei‐Jun; Zhao, Zeang; Chen, Mingji; Yang, Yazheng; Chen, Haosen; Fang, Daining (Advanced functional materials, 2020)
Origami structures offer valuable applications in many fields, ranging from metamaterials to robotics. The multistable characteristics of origami structures have been pursued for acquiring unique reconfigurable features. For achieving this goal, an unusual polymeric tristable origami structure is demonstrated using a classic square‐twist origami configuration. By manipulating both material properties and geometric parameters of the heteropolymer structures, a design principle for tailoring the multistable configuration in the square‐twist origami is established based on variation of the structural potential energy. Under thermal triggering, the stiffness of the deformable structure is dramatically reduced, which causes an increase in the structural degree of freedom, allowing for self‐deployment via release of the prestored energy in the elastic twisted hinges. Utilizing such unique features and design principles, a prototype of frequency reconfigurable origami antenna of five diverse operating modes and a programmable multiple‐input multiple‐output communication system is subsequently designed and assembled, aiming to substantially promote the channel capacity and communication reliability. The findings and results firmly provide a remarkable design principle and strategy for advancing active origami structures and devices in shape‐morphing systems. Active reconfigurable tristable square‐twist origami structures are fabricated via a multimaterial 3D print method via a self‐deployment phenomenon under thermal stimuli. Designing different geometries allows for square‐twist origami structures with different stable states. These structures can be used as a deformable dielectric substrate to compose a frequency reconfigurable origami antenna, and the function of one origami antenna instead of five conventional antennas can be realized.